2020
DOI: 10.4193/rhin19.371
|View full text |Cite
|
Sign up to set email alerts
|

EGFR mutation and HPV infection in sinonasal inverted papilloma and squamous cell carcinoma

Abstract: Background: To evaluate the involvement of EGFR signalling and HPV infection in a cohort of inverted sinonasal papilloma (ISP) and sinonasal squamous cell carcinoma (SNSCC) and their value for prognosis and clinical treatment. Methods:We analysed 55 ISP, 14 SNSCC associated with ISP (SNSCC-isp) and and 60 SNSCC not associated with ISP (SNSCC-novo) for EGFR gene mutation and copy number gain, protein expression of EGFR and phosporylated EGFR (pEGFR), and HPV-infection and KRAS mutation. Findings were correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
26
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 26 publications
9
26
4
Order By: Relevance
“…Human papillomavirus (HPV), indeed, plays a role in SNSCCs. Analyzed as part of a previously published study by our group, 10% (5/50) of our cases were found positive [39], similar to other SNSCC studies [40][41][42]. These HPV-positive cases may be thought to escape immune surveillance.…”
Section: Discussionsupporting
confidence: 85%
“…Human papillomavirus (HPV), indeed, plays a role in SNSCCs. Analyzed as part of a previously published study by our group, 10% (5/50) of our cases were found positive [39], similar to other SNSCC studies [40][41][42]. These HPV-positive cases may be thought to escape immune surveillance.…”
Section: Discussionsupporting
confidence: 85%
“…In the literature, EGFR mutations have been hitherto demonstrated in 38 to 88% of ISPs [ 3 , 16 ] and in 50 to 88% of ISP-associated SSCCs [ 10 , 16 ]: Cabal et al found EGFR exon 20 mutations in 38% (7/18) of ISPs and in 50% (6/12) of ISP-associated SSCCs, while EGFR exon 20 mutations in ISP-unassociated SSCC occurred in only 5.3% (1/19) [ 16 ]. Sasaki et al reported EGFR mutation in 100% (9/9) of ISPs and 83% (10/12) of ISPs associated with SSCC, the vast majority being exon 20 insertions.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found similar rates. Udager et al found an HPV‐positivity rate of 27.8% among SNSCCs, while Cabal et al found a rate of 20% 13,14 . A 2013 systemic review and meta‐analysis by Syrjänen and Syrjänen examining 492 SNSCCs across 35 studies found an HPV‐positivity rate of 27%, 15 while the previously mentioned study by Oliver et al found an HPV‐positivity rate of 31.5% 10 .…”
Section: Discussionmentioning
confidence: 95%